2000
DOI: 10.1212/wnl.55.5.624
|View full text |Cite
|
Sign up to set email alerts
|

The impact of migraine on quality of life in the general population

Abstract: Migraineurs report more asthma and chronic musculoskeletal pain. Compared with nonmigraineurs and to others with chronic conditions, migraineurs report compromised physical, mental, and social functioning, particularly those with a high frequency of attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
256
1
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(283 citation statements)
references
References 32 publications
19
256
1
7
Order By: Relevance
“…Monzon and Lainez [6] showed lower SF-36 scores for migraine patients compared to healthy controls across all 8 domains. A population-based study using the RAND-36 (a Dutch translation of the SF-36) similarly demonstrated decreased scores on all 8 health domains for migraineurs [7]. We have observed a comparable trend with statistically significant reductions in all 8 subscales for subjects with migraine compared to their non-migraine counterparts.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Monzon and Lainez [6] showed lower SF-36 scores for migraine patients compared to healthy controls across all 8 domains. A population-based study using the RAND-36 (a Dutch translation of the SF-36) similarly demonstrated decreased scores on all 8 health domains for migraineurs [7]. We have observed a comparable trend with statistically significant reductions in all 8 subscales for subjects with migraine compared to their non-migraine counterparts.…”
Section: Discussionsupporting
confidence: 65%
“…HRQOL measurement tools communicate the impact of illness on the patient's well-being, providing unique insight into the evaluation and management of migraine. Previous studies have indicated significant reductions in HRQOL among subjects with migraine [5][6][7][8][9][10]. Despite the episodic nature of migraine, HRQOL has been shown to be comparable to living with chronic diseases such as diabetes and arthritis [5].…”
mentioning
confidence: 99%
“…Both our study [3] and that of Lipton et al [18] found that headache frequency was an important predictor of HRQoL.…”
Section: Migraine Quality Of Life and Depressionsupporting
confidence: 71%
“…In a large Dutch population-based study, we compared the HRQoL of migraineurs and non-migraineurs [3]. HRQoL of Abstract Population-based studies have shown that migraineurs have reduced HRQoL independent of depression.…”
Section: Impact Of Migraine On Hrqol In the General Populationmentioning
confidence: 99%
“…However, patients with chronic headaches complain about signifi cant well-being impairment with damage in their quality of life 11 . Most studies have reported the consequences of migraine in the quality of life [12][13][14][15][16][17] ; few reported the quality of life of patients with CDH [18][19][20][21][22] . When compared to the general population, the patients with CDH present signifi cant reduction in all SF-36 domains 22 .…”
mentioning
confidence: 99%